KOMPOSISI SAMPAH LAUT (MARINE DEBRIS) DI KAWASAN PESISIR BARAT PANTAI AMPENAN KOTA MATARAM - Chandrika Eka Larasati; Ayu Adhita Damayanti; Nurliah Nurliah; Baiq Hilda Astriana; Ibadur Rahman (Universitas Bengkulu, 2022)
Marine debris is a material wasted intentionally or unintentionally into coastal and marine environment caused by human activities. Trash has become one of the biggest contributors to coastal and marine pollution that may disrupt the balance of aquatic ecosystem, reduce the aesthetic value of coastal and marine areas, and even disturb human health. This research was conducted to provide information regarding type, weight, and source of trash found around western coastal area of Ampenan Beach, Mataram City. Sampling spots which represented a condition of study area were determined using purposive sampling. Two research locations were chosen around Ampenan Beach, namely Penghulu Agung Beach and estuary of Jangkok River. Trash collection was done done using line transect method based on criteria determined from length of the coastline. The trash collected was then sorted, weighed, and identified based on trash classification system. Marine trash found around the research locations, both at Penghulu Agung Beach (Stasion 1) and at estuary of Jangkok River (Station 2), was dominated by plastics with an average number of trash pieces, respectively, of 7 item/m2 and 9 items/m2. Meanwhile, the weights of plastic trash found at station 1 and 2, respectively, were 29,76 gr/m2 and 213 gr/m2. The amount of plastic trash found at research locations might be the impact of human activities throwing the trash into the estuary and the beach.